Effects of a forced sedentary behaviour on the physical fitness of top level wheelchair basketball players - Bernardi, M.; Ciccarelli, A.; Peluso, I.; Cavedon, V.; Castellucci, F.; Bellito, S.; Milanese, C.; Toti, E.; Raguzzini, A.; Cavarretta, E. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: To examine the effects of a relative sedentary behaviour (SB) due to the CoViD-19 related lockdown (LD) on all components of physical fitness (PF) in wheelchair basketball players (WBP) with different locomotor impairments (impaired muscle strength, limb deficiency and impaired passive range of motion). METHODS: A comprehensive PF evaluation (1) was performed on twelve male WBP recruited from the Italian national team at the peak of their PF (June 2019, PRE) and after the LD (June 2020, POST), in both cases after the end of the national major league championship. PF evaluation included anthropometry (body mass and skinfold measurements) to assess fat mass, cardiopulmonary incremental maximal arm cranking exercise (ACE) test (CPET) to measure oxygen uptake peak (VO2peak), supramaximal (130% of the power peak reached in the CPET) up to exhaustion ACE test to estimate maximal glycolytic anaerobic capacity, 10-second-long "Wingate" all out ACE Test to estimate anaerobic peak power and handgrip measurements (HG) to assess maximal strength. Similarly to the typical training modality previously carried out in the gym, strength training was prescribed at the beginning of the LD period (for a minimum of three times per week, bench press, triceps extension, dumbbell row, biceps curl, lateral raises, dumbbell shrugs, abdominal crunch carried out 12 repetitions for 4 sets at 50% of the one repetition maximum). WBP were asked to fill in a questionnaire regarding their home and possible out-door training. Dietary advice was provided to WBP during the LD. RESULTS: The self-reported aerobic training performed during the LD by our WBP was very law compared to the typical aerobic training (9.6±4.96 to 2.4±3.67 hours per week) which included typically wheelchair basketball training in field. An higher strength training volume was obtained during the LD period. Comparing PRE vs POST LD significant results (p